Cognitive evaluation for conceptual design: cognitive role of a 3D sculpture tool in the design thinking process. Issue 4 (2nd October 2018) - Lee, Jeehyun; Ahn, Jiwon; Kim, Jieun; Kho, Jeong Min; Paik, Hyo Yon
ABSTRACT: This study focuses on the decisive role played by the digital design environment in the cognitive design process and design thinking. To analyse the cognitive role of digital design tools, we carried out a protocol analysis of conventional design sketching and a 3D sculpture tool. Cognitive evaluation was a differentiating factor when considering the contextual role of the 3D sculpture tool in subsequent evaluations, non-sequential evaluations for conversion, and passive approaches within the design process. Cognitive evaluation played the following roles: validation, extension, navigation, exploration, and confirmation. The navigation, exploration, and extension roles played by non-sequential evaluation were mainly related to inductive design thinking. Finally, the types of cognitive evaluation and their roles when using the 3D sculpture tool were different, according to the design thinking type. This study explored the multidimensional roles of cognitive evaluation using a 3D sculpture tool and its relationship with design thinking types.